Normative anthropometry and proportions of the Kenyan-African face and comparative anthropometry in relation to African Americans and North American Whites - Saurab S. Virdi; David Wertheim; Farhad B. Naini (SpringerOpen, 2019)
Abstract Background There is no normative craniofacial anthropometric data for the Kenyan-African population. The purpose of this investigation was to determine normative anthropometric craniofacial measurements and proportional relationships for Kenyans of African descent and to compare the data with African Americans (AA), North American Whites (NAW), and neoclassical canons. Methods Twenty-five direct facial anthropometric measurements, and 4 angular measurements, were taken on 72 Kenyan-African participants (age range 18-30 years) recruited at the University of Nairobi in Kenya. The data were compared with AA and NAW populations, and neoclassical canons. Descriptive statistics of the variables were computed for the study population. Results Significant differences between both Kenyan males and females were detected in forehead height (~ 5 mm greater for males, ~ 4.5 mm for females), nasal height (reduced by ~ 4 mm in males, ~ 3 mm in females), nasal width (8-9 mm greater), upper lip height (> 3 mm), and eye width (greater by ~ 3 mm) compared to NAW subjects. All vertical measurements obtained were significantly different compared with NAW. Differences were observed in comparison with AA subjects, but less marked. Mouth width was similar in all groups. Angular measurements were variable. Neoclassical canons did not apply to the Kenyan population. Conclusions Anthropometric measurements of NAW showed clear differences when compared with the Kenyan population, and variations exist with comparative AA data. The anthropometric data in terms of linear measurements, angular measurements, and proportional values described may serve as a database for facial analysis in the Kenyan-African population.